Pemberdayaan Ibu Siaga Terhadap Tingkat Kemandirian Pencegahan Dan Keterampilan Perawatan Balita Pneumonia - Rosuliana, Novi Enis; Nurhayati, Tetik (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
Pneumonia is an acute infectious disease of the lower respiratory tract (alveoli). Pneumonia cases in Indonesia in 2018 reached 20.06%, while West Java was 4.62% above the national case estimate. The risk factors for pneumonia are exclusive breastfeeding, malnutrition, immunization status, history of LBW, smoking, economy, and home environment. The purpose of the study was to determine the effect of empowering alert mothers on the independence of prevention and care skills of pneumonia under five. The research design is a quasi-experimental pre-test and post-test with a control group design. The population is all mothers who have toddlers in the sub-village of Ciamis Regency with a total of 100. The research sample consisted of 60 respondents divided into the intervention group and the control group with consecutive sampling. The research instrument is in the form of a pneumonia prevention independence questionnaire and pneumonia care skills for toddlers. Data were analyzed using Wilcoxon Signed Ranks and Mann-Whitney U Test. The results showed a p-value of 0.000 p-value of 0.05, indicating the effect of empowering alert mothers on the independence level of prevention and care skills of pneumonia under five. Further research relates the application of complementary therapy to the treatment of pneumonia under five is needed.